2020
DOI: 10.1073/pnas.2001403117
|View full text |Cite
|
Sign up to set email alerts
|

Land use and climate change impacts on global soil erosion by water (2015-2070)

Abstract: Soil erosion is a major global soil degradation threat to land, freshwater, and oceans. Wind and water are the major drivers, with water erosion over land being the focus of this work; excluding gullying and river bank erosion. Improving knowledge of the probable future rates of soil erosion, accelerated by human activity, is important both for policy makers engaged in land use decision-making and for earth-system modelers seeking to reduce uncertainty on global predictions. Here we predict future rates of ero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
428
0
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 855 publications
(453 citation statements)
references
References 38 publications
5
428
0
20
Order By: Relevance
“…The meaning of the soil quality index (SQI) is the ability of the soil to function within an ecosystem boundary, whether managed or natural, and to achieve sustainability of crop productivity while maintaining soil from degradation processes [5,6]. In many regions around the world, soil quality is declining rapidly [7], due to many reasons, including, but not limited to, changes in land use types with intensive land use [8,9]. Therefore, the assessment of SQ is considered the basis for monitoring and maintaining the sustainability of agricultural systems [10].…”
Section: Introductionmentioning
confidence: 99%
“…The meaning of the soil quality index (SQI) is the ability of the soil to function within an ecosystem boundary, whether managed or natural, and to achieve sustainability of crop productivity while maintaining soil from degradation processes [5,6]. In many regions around the world, soil quality is declining rapidly [7], due to many reasons, including, but not limited to, changes in land use types with intensive land use [8,9]. Therefore, the assessment of SQ is considered the basis for monitoring and maintaining the sustainability of agricultural systems [10].…”
Section: Introductionmentioning
confidence: 99%
“…15 Changes in temperature and precipitation will impact plant biomass production, infiltration rate, soil moisture, land use, and crop management and hence affect runoff and soil erosion. 16 According to Borrelli et al, 17 global water erosion due to climate change could increase by up (+30% to +66%) over the next 50 years. The study (Moges et al 18 ) reported that Ethiopia is 1 of the countries highly affected by increased soil erosion due to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…For soil C stores, reduced extreme cold and extreme rainfall present the largest risk. Continuation of this trend will have large implications for the C cycle and is likely to increase the release of soil C and decrease sequestration through increased wet–dry cycles, microbial respiration and erosion losses (Schimel et al ., 2007; Kim et al ., 2012; Reichstein et al ., 2013; Petrakis et al ., 2017; Borrelli et al ., 2020) (Table 1). Our analysis also indicates that large expanses of upland bog or lowland fen peat are located in regions experiencing higher temperatures, droughts and therefore potential fire risk.…”
Section: Resultsmentioning
confidence: 99%